Autolysis in Staphylococcus aureus: Preferential Release of Old Cell Walls - Gilpin, R. W. (1974)
The kinetics of release of old versus new cell wall in two strains of Staphylococcus aureus were studied during autolysis. In both strains the autolytic enzyme is an amidase. Cells were double labeled with (3)H and (14)C, and the distribution of radioactivity in the cell walls was monitored during autolysis. In all cases the rate of release of steady-state lable from peptidoglycan was significantly higher than that of pulse label. Identical results were obtained with whole cells or isolated cell walls. The results suggest that in S. aureus the old cell wall is preferentially released during autolysis.